Mitigating end-stage fatigue: Acute inhaled salmeterol preserves sprint power in simulated cycling - Merlini, M.; Staiano, W.; Angius, L.; Romagnoli, M.; Schena, F.; Dickinson, J.; Marcora, S. (Scandinavian Journal of Medicine & Science in Sports, 2025)
This study tested whether a single 100 µg inhalation of salmeterol enhances 12-s sprint performance in both fresh and fatigued states in elite road cyclists. In a randomized crossover design, 16 well-trained, non-asthmatic male cyclists completed 2 trials 1 week apart. Participants inhaled either 100 µg salmeterol or placebo 1h before testing. Each trial involved: an initial 12-s sprint (fresh), a 1h race simulation (40%-95% peak power output) with heart rate, blood lactate concentration, and rating of perceived exertion (RPE) monitored, and a final 12-s sprint (fatigued). Peak and mean power, and vastus lateralis myoelectric activity were recorded during the sprints. Power declined from pre- to post-simulation in both conditions (p < 0.016), but the decrement was attenuated with salmeterol (peak: -7.5% vs. -18.2%; mean: -13.0% vs. -19.8%). Fatigued-sprint peak power was higher with salmeterol (915 ± 135 W) than placebo (831 ± 112 W; p = 0.030), as was mean power (692 ± 76 vs. 643 ± 92 W; p = 0.037). No effect of salmeterol was observed on fresh sprint performance and myoelectric activity. Blood lactate concentration and RPE rose similarly in both conditions (p < 0.001), while heart rate was higher with salmeterol during the first 20 min (p = 0.004). Acute inhalation of salmeterol attenuates muscle fatigue and enhances sprint performance at the end of a simulated race. These findings challenge the presumption of no enhancing effect of inhaled salmeterol at therapeutic doses in competitive road cycling, where final sprints often determine outcomes.